(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
The article presents the results of empirical research on the relationship of creativity and success of students in higher education, which is possible to trace the dependence of the level of success of students learning the nature of their creativity. It was found that the relationship between the two phenomena (creative and intellectual) - straight, but weak: the level of development of creativity of adolescents person has direct impact on the level of educational achievements.